2007
DOI: 10.1111/j.1532-5415.2007.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Resident Outcomes in Small‐House Nursing Homes: A Longitudinal Evaluation of the Initial Green House Program

Abstract: The GH is a promising model to improve quality of life for nursing home residents, with implications for staff development and medical director roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
275
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 295 publications
(290 citation statements)
references
References 18 publications
(33 reference statements)
6
275
1
3
Order By: Relevance
“…Autonomy and privacy were strongly linked (separate flats) and involved a lower degree of supervision in extra-care housing compared to the density of the assisted living, where residents could refrain completely from autonomy if they preferred to. This is in line with Kane and colleagues’ study (2007) in which autonomy and privacy were aspects of quality of life which was found to be higher in the small-house nursing home with private flats. This is a reasonably direct and discernible cause–effect mechanism.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Autonomy and privacy were strongly linked (separate flats) and involved a lower degree of supervision in extra-care housing compared to the density of the assisted living, where residents could refrain completely from autonomy if they preferred to. This is in line with Kane and colleagues’ study (2007) in which autonomy and privacy were aspects of quality of life which was found to be higher in the small-house nursing home with private flats. This is a reasonably direct and discernible cause–effect mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…The importance of architectural space for the provision of resident-centred care has been a point of departure in existing research, although without any particular analysis or discussion (Kane et al, 2007; Molony et al, 2011). This study shows how architectural space contributes to the emergence of resident-centred care, and the results show that it appears in different forms in different architectural environments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations